Penerapan Pendekatan Taktis pada Aktivitas Pembelajaran Bola Basket - Midtsaluna, Cselia; Nugraha, Eka; Gumilar, Agus; Hambali, Burhan; ., Salman (Journal of SPORT (Sport, Physical Education, Organization, Recreation, and Training), 2024)
This research is based on facts about the field of learning and the current state of physical education which still tends to use traditional approaches. The traditional learning process tends to make students bored and less enthusiastic about participating in the learning process. This research was conducted to determine the contribution of the tactical approach to students' playing skills. This research uses experimental methods to study it. This research design is pre-experimental, a design in which only one group or class is given pre- and post-tests. The student subjects who will be involved are high school students in the Bandung City area who take part in basketball extracurriculars. The results of the analysis prove that tactical approach learning in basketball learning activities has a significant effect on students' playing performance.